Critical Elements of Emotional Quotients (EQ) During and After Crisis among Malay Women Food Operators in Klang Valley - Shima Abdul Rani, Nazatul; K. , Sarojini Krishnan; Suradi, Zurinah (International Journal of Psychosocial Rehabilitation, 2020)
This paper highlighted the elements of emotional quotients among female or female food operators in Klang Valley, Malaysia, during and after the economic crisis. Emotional quotients are divided into five elements, which are self-awareness, self-regulation, self-motivation, empathy, and social skills. About 100 questionnaires were distributed around Kampung Baru, Sentul, Keramat, Wangsa Maju, and Ulu Kelang in Klang Valley, Malaysia. The data were collected in October 2017. Most women food operators agreed that during the economic crisis the most important elements of emotional quotients are social skills, self-regulation, self-motivation, self-awareness, and empathy. However, after the economic crisis, most women entrepreneurs agreed that the most important elements are self-motivation, self-awareness, social skills, self-regulation, and empathy. Hence, from the study, we can conclude that in order to survive during an economic crisis, women entrepreneurs should be focusing more on their social skills, which are getting cooperation from employees, having a special unit to communicate with employees, the ability to communicate with employees, the ability to inspire employees, and the ability to evaluate the abilities of employees. However, after the economic crisis, they will be focusing more on being self-motivated, which includes the ability to control operation costs, to keep employee interest, to stay positive, to ensure business operations run smoothly, and to keep a positive culture in the business.